Communicating with Communicators - S. H. Wittwer (Journal of Applied Communications, 1976)
Sixty years ago there were fewer than 100 million people in the United States. Half of them lived on farms and in communities of 2500 or less. The farm population was a third of the total, or 32 million. We had a farm labor force of about 12 million. By 1950 it was reduced to 7 million. Today, it's 4.6.